A Borondifluoride‐Complex‐Based Photothermal Agent with an 80 % Photothermal Conversion Efficiency for Photothermal Therapy in the NIR‐II Window. Issue 41 (20th August 2021) - Jiang, Zhiyong; Zhang, Changli; Wang, Xiaoqing; Yan, Ming; Ling, Zongxin; Chen, Yuncong; Liu, Zhipeng
Abstract: Small organic photothermal agents (SOPTAs) that absorb in the second near‐infrared (NIR‐II, 1000–1700 nm) window are highly desirable in photothermal therapy for their good biocompatibility and deeper tissue penetration. However, the design of NIR‐II absorbing SOPTAs remains a great challenge. Herein, we report that molecular engineering of BF2 complex via strengthening the donor‐acceptor conjugation and increasing the intramolecular motions is an efficient strategy to achieve NIR‐II absorbing SOPTAs with high photothermal performance. Based on this strategy, a BF2 complex, BAF4, was designed and synthesized. BAF4 exhibits an intense absorption maximum at 1000 nm and negligible fluorescence. Notably, the nanoparticles of BAF4 achieve a high photothermal conversion efficiency value of 80 % under 1064 nm laser irradiation (0.75 W cm −2 ). In vitro and in vivo studies reveal the great potential of BAF4 nanoparticles in photoacoustic imaging‐guided photothermal therapy in the NIR‐II window. Abstract : A NIR‐II absorbing BF2 complex with high photothermal performance was designed. The complex achieves a high photothermal conversion efficiency value of 80 % under 1064 nm laser irradiation. In vivo studies reveal the great potential of the complex in photoacoustic imaging‐guided photothermal therapy in the NIR‐II window.